Understanding the bitterness of Wassily Leontief: Intention and reception of input-output techniques, 1940s-1950s - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2022)
Leontief was and still is one of the most recognized names in economics, inextricably linked to the development of input-output techniques, but throughout his life he remained fiercely critical of other economists' works and of the state of economic science. To understand his bitterness, we go back to the root of the split between Leontief and the rest of the economics profession, through an examination based on new archival material of the debates that took place in the late 1940s. We show that these debates were concerned with the core of the practice of economists, the conduct of economic policy and the relation between rational individuals and the economy as a whole. From his input-output model, conceived as an operational theory of economic interdependencies, Leontief drew a specific approach to economic policy and planning which had a lot of success with government agencies, explaining how he could durably sustain his split from the profession.
Keywords: 330; Input-Output-Analyse; Wirtschaftspolitik; Wirtschaftstheorie